Casos y cosas: semanario popular (Vol. 2, No. 49) - Imprenta La Region (My University, 1920)
SPANISH: Incluye: Para la historia, Bombos que caen en el vacío..., De confesonario, Ni para descalzarlo..., Carta abierta, Nociones de esgrima, Cicinas de fierro.

ENGLISH: For history, drums that fall into the void..., of confessional, not even to take off his shoes..., open letter, fencing notions, iron kitchens.
Cases and things: popular weekly (Vol. 2, No. 49)
Keywords: Periodicals; Satire, Peruvian; Humor; Iquitos (Perú)--revistas; Perú--revistas satíricas